Reversible Thermal Hysteresis in Heating‐Cooling Cycles of Magnetic Susceptibility: A Fine Particle Effect of Magnetite - Zhang, Qi; Appel, Erwin (Geophysical research letters, 2023)
Thermomagnetic curves of magnetic susceptibility (κ) are key to characterizing magnetic properties. We report hump‐shaped κ‐T curves of magnetite‐bearing basalt during heating‐cooling cycles to ∼340°C, with a large thermal hysteresis and similar starting and ending values, even in multiple repeated cycles, ruling out changes in magnetic mineralogy. Based on FORC diagrams and published results of engineered materials, we propose that thermal hysteresis arises from configurations of magnetic moments in clusters of single‐domain particles due to dipolar coupling, with different collective behavior during heating and cooling. This effect modifies the hump‐shaped thermal relaxation behavior of the individual nanoparticles. FORC and κ‐T results indicate an increase in effective particle sizes after 700°C‐heating. Our results are a warning against premature interpretation of a decreasing trend in κ‐T curves by maghemite inversion. Instead, fine particle behavior should be considered when a hump‐shaped κ‐T behavior is detected. Plain Language Summary Thermomagnetic curves of magnetic susceptibility (κ) are key to characterizing magnetic properties. A marked drop in κ‐T curves at ∼300–400°C is often considered to indicate the inversion of maghemite to hematite. Such a drop is often preceded by an increase in κ, creating a hump shape that is rarely noted in discussions. We report hump‐shaped κ‐T curves in magnetite‐bearing basalt. When heating up to ∼340°C and cooled subsequently, a large thermal hysteresis was observed. This hump shape and the thermal hysteresis behavior occur in a very similar way in repeated κ‐T cycles, ruling out changes in magnetic mineralogy. We hypothesize that the thermal hysteresis arises from configurations of coupled magnetic moments in clusters of fine particles, which is partly irreversible upon cooling. This effect modifies the hump‐shaped thermal relaxation behavior of the individual particle moments. When heated to 700°C, grain boundaries may weld and internal stress effects are reduced, increasing the effective particle sizes and shifting the hump‐peak to a higher temperature. Our results indicate that fine particle behavior should be considered for all types of natural materials when a hump‐shaped κ‐T curve is observed rather than interpreting the drop in κ as maghemite inversion. Key Points We observed reversible thermal hysteresis behavior in hump‐shaped partial magnetic susceptibility cycles of magnetite‐bearing basalts The thermal hysteresis may be caused by blocked states of coupled nanoparticle moments modulating thermal activation Descending susceptibility in hump‐shaped curves is often due to single‐domain thermal relaxation rather than maghemite inversion